Experiences of Female Community Health Volunteers Regarding Maternal and Newborn Care in Kaski District - Ghimire, Rajina; Mukhia, Suzanna (Journal of Nursing Education of Nepal, 2024)
Introduction: Female Community Health Volunteer plays vital role in maternal and newborn health of community. Despite being a backbone of health care system of Nepal to reduce maternal and neonatal mortality they are facing different challenges from family, and community while performing their role. Limited studies are being done in this area, so the researcher aimed to explore the experiences of female community health volunteer while performing their role. Method: A Hermeneutic Phenomenology design was used to collect data from purposively selected twelve Female Community Health Volunteers of Pokhara-11, Kaski district. Data was collected by in-depth interview method using semi-structured interview guidelines. Ethical approval for the study was obtained from the Institutional Review Committee. Data was transcribed and analyzed using the seven-step Collaizi method. Findings: After analysis of the experiences of study participants emerged eight themes and twenty-nine sub themes. The themes were providing antenatal care, postnatal and newborn care, under-five children care, cross-cutting maternal and newborn health activities, motivating factors, challenges, expectation of female community health volunteers and communication system. People praise and accept their health advice and visit health centers for care. Conclusion: It is concluded that the participants have experienced both motivation and barriers from family, community and health institutions while providing care to the community. Some people listen and praise their effort and follow their health advice while some ignore them. Good health of mother and child bring dedication to continue to serve the people. The study provided comprehensive information on members working in grassroot level of health and will help local leaders to use these findings for enhancing their performance by addressing their problems.